Reactivity Properties of Mixed- and High-Valent Bis(μ-Hydroxide)-Dinickel Complexes - McDonald, Aidan (My University, 2021)
Despite their potential role in enzymatic systems, there is a dearth of hydroxide-bridged high-valent oxidants. We recently reported the synthesis and characterization of NiIINiIII(μ-OH)2 (2) and Ni2 III(μ-OH)2 (3) species supported by a dicarboxamidate ligand (N,N'-bis(2,6-dimethyl-phenyl)-2,2-dimethylmalonamide). Herein, we explore the oxidative reactivity of these species using a series of para-substituted 2,6-di-tert-butyl-phenols (4-X-2,6-DTBP, X = -OCH3, -CH2CH3, -CH3, -C(CH3)3, -H, -Br, -CN, and -NO2) as a mechanistic probe. Interestingly, upon reaction of 3 with the substrates, the formation of a new transient species, 2', was observed. 2' is postulated to be a protic congener of 2. All three species were demonstrated to react with the substituted phenols through a hydrogen atom transfer reaction mechanism, which was elucidated further by analysis of the postreaction mixtures. Critically, 3 was demonstrated to react at far superior rates to 2 and 2', and oxidized substrates more efficiently than any bis-μ-oxo-Ni2 III reported to date. The kinetic superiority of 3 with respect to 2 and 2' was attributed to a stronger bond in the product of oxidation by 3 when compared to those calculated for 2 and 2'.
PUBLISHED